Answer :

__Basic idea:__

√Second order derivative is nothing but derivative of derivative i.e.

√The idea of chain rule of differentiation: If f is any real-valued function which is the composition of two functions u and v, i.e. f = v(u(x)). For the sake of simplicity just assume t = u(x)

Then f = v(t). By chain rule, we can write the derivative of f w.r.t to x as:

√Product rule of differentiation-

√Apart from these remember the derivatives of some important functions like exponential, logarithmic, trigonometric etc..

Let’s solve now:

Given, y = …..equation 1

As we have to prove : ..

We notice a second-order derivative in the expression to be proved so first take the step to find the second order derivative.

Let’s find

As

So, lets first find dy/dx and differentiate it again.

As y is the product of two functions u and v

Let u = log x and v = 1/x

Using product rule of differentiation:

[∵ log x) = & ]

Again using the product rule to find :

[∵ log x) = & ]

∴ ….. proved

Rate this question :

If y = tan^{-1}x, find in terms of y alone.

If y = sin^{-1} x, show that

If y = 3 cos(log x) + 4 sin(log x), show that

Mathematics - Board Papers

If x = t^{2}, y = t^{3}, then is

If x = a cos θ + b sin θ, y = a sin θ – b cos θ, show that

Mathematics - Board PapersIf prove that

Mathematics - Exemplar

If y =(tan^{–1}x)^{2}, show that

If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}